Phenylketonuria: A Comprehensive Review of Pathophysiology, Diagnosis, and Management Strategies - Konopka, Agata; Szczepaniak, Zuzanna; Wdowiak, Natalia; Ziółkowska, Dominika; Adamska, Kinga; Lissak, Karina (Quality in Sport, 2024)
Introduction: Phenylketonuria (PKU) is a genetically determined congenital metabolic disorder characterized by the body's inability to properly metabolize the amino acid phenylalanine, which is ingested through food. This deficiency leads to the accumulation of phenylalanine in the blood. If untreated, this can result in neurological damage and cognitive impairments. Despite significant progress in understanding the disease, along with advancements in diagnostic methods, the fundamental approach to managing PKU has remained consistent: early detection and adherence to a diet low in phenylalanine are essential to preventing the adverse effects of the disorder. Purpose of the work: The aim of the study is to analyze and present the current knowledge about phenylketonuria and the quality of life of patients suffering from this disease, as well as methods of its detection. Materials and methods: An analysis of research papers available on PubMed and Google Scholar was undertaken using the following keywords: phenylketonuria; PKU diagnosis; phenylketonuria newborn screening; genetic testing for PKU; Quality of Life in PKU patients. Results: There are various diagnostic methods used in newborn screening and to confirm diagnosis. Regardless of the method, early diagnosis and the introduction of an appropriate diet are crucial. Adherence to dietary restrictions and monitoring phenylalanine levels, along with managing the effects of elevated levels in the body, may negatively impact the quality of life for individuals affected by PKU.